Pengaruh Pijat Tui Na Terhadap Peningkatan Berat Badan Bayi Usia 1-6 Bulan - Indriastuti, Aprilia; Jasmawati, Jasmawati; Nulhakim, Lukman (Bunda Edu-Midwifery Journal (BEMJ), 2024)
According to UNICEF, the infant mortality rate up to 1 year is 28.2 per 1,000 live births. Malnutrition and malnutrition are the leading causes of death. One non-drug treatment that can be done is Tui Na massage.Objectives The objective of this study was to determine the effect of tuin massage application on the weight gain of infants aged 1 to 6 months at Karang Asam Public Health Center. Research Methods The study was a quasi-experimental study with a pre- and post-trial design and a control group. The study sample consisted of 10 people from each group. Intentional sampling was used in this study. Wilcoxon test, dependent T test and Mann Whitney test were used for statistical tests. Significance (p) values ​​are 0.005 and 0.000 (p less than α) Meanwhile, using Mann Whitney, another test value is obtained as a p-value of 0.364 (p more than α). The introduction of tui na massage affected the birth weight of infants aged 1-6 months at Karang Asam Public Health Center with a value of ρ of 0.000 in the treatment group. Healthcare workers should provide the community with the educational stimulation of tui na massage to gain weight for the baby .